Unusual presentation of markedly elevated transaminase levels in a triple viral infection: A case report - N/A, Arpan; Singh, Navrajbir; Singh, Jaspreet; Bali, Kusum; N/A, Akshit (Indian Journal of Case Reports, 2025)
We report a rare and unusual case of a 21-year-old male presenting with extremely elevated transaminase levels secondary to co-infection with cytomegalovirus, Epstein–Barr virus, and herpes simplex virus. Despite being immunocompetent, the patient displayed an extraordinary liver enzyme profile, with aspartate transaminase levels of 17,598 U/L and alanine transaminase of 13,666 U/L, significantly higher than what is typically observed in viral hepatitis. This case highlights the rare phenomenon of triple viral hepatitis leading to such profound liver injury and emphasizes the importance of considering multiple viral infections in patients with unexplained hepatic injury and severely deranged liver function tests.